2015
DOI: 10.5888/pcd12.150079
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Patterns of Health Care Travel Among Inpatients Diagnosed With Congestive Heart Failure, Florida, 2011

Abstract: IntroductionCongestive heart failure (CHF) is a major public health problem in the United States and is a leading cause of hospitalization in the elderly population. Understanding the health care travel patterns of CHF patients and their underlying cause is important to balance the supply and demand for local hospital resources. This article explores the nonclinical factors that prompt CHF patients to seek distant instead of local hospitalization.MethodsLocal hospitalization was defined as inpatients staying w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The comparison among racial/ethnic subgroups reveals that mobility for seeking hospital services is more limited for blacks and Hispanics than for whites and Asians. Compared with a previous study focusing on the healthcare travel patterns of only congestive heart failure patients (Jia and Xierali 2015), this study found a similar pattern among racial/ethnic groups. The longest average travel time by Native Americans should be interpreted with caution due to a smaller sample size of this group.…”
Section: Discussionsupporting
confidence: 67%
“…The comparison among racial/ethnic subgroups reveals that mobility for seeking hospital services is more limited for blacks and Hispanics than for whites and Asians. Compared with a previous study focusing on the healthcare travel patterns of only congestive heart failure patients (Jia and Xierali 2015), this study found a similar pattern among racial/ethnic groups. The longest average travel time by Native Americans should be interpreted with caution due to a smaller sample size of this group.…”
Section: Discussionsupporting
confidence: 67%
“…Geographic information system‐based network analysis refers to all spatial analyses conducted on the basis of a real‐road network. It offers a way to identify the shortest or any path between addresses (or between centroids for areas ) and estimate the travel distance, or expected travel time, if the speed limit or other traffic information is provided. More than one‐third (48 of 121, 39.7%) of the reviewed studies used network analysis (Appendix S1).…”
Section: Resultsmentioning
confidence: 99%
“…The first research strand challenges this assumption by demonstrating that the simultaneous examination of spatial and social service accessibility factors describes service accessibility better than combining spatial and social service accessibility research studies. (Jia & Xierali, 2015;Schultheis, 2014;Wang & Luo, 2005).…”
Section: An Implicit Challenge Of the User/type Cross-sectionmentioning
confidence: 99%
“…Existing research describes how the user/type cross-section fails to capture the factors that mediate service accessibility (Hawthorne & Kwan, 2012;Jia & Xierali, 2015;Schultheis, 2014;Wang & Luo, 2005). This research attempts to explicitly invalidates the user/type cross-section and connect service accessibility research with the reality of service usage.…”
Section: Chapter 3: Socio-spatial Entanglement Theorymentioning
confidence: 99%